2019
DOI: 10.1101/865949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nucleus measures shape deformation for cellular proprioception and regulates adaptive morphodynamics

Abstract: The physical microenvironment regulates cell behavior during tissue development and homeostasis. How single cells decode information about their geometrical shape under mechanical 20 stress and physical space constraints within their local environment remains largely unknown. Here we show that the nucleus, the biggest cellular organelle, functions as a non-dissipative cellular shape deformation gauge that enables cells to continuously measure shape variations on the time scale of seconds. Inner nuclear membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Relying on this ruler, cells can measure the degree of their environmental confinement and rapidly tailor specific behaviors to adapt to the confinement at time scales shorter than those associated with changes in gene expression. In the context of cell migration, such tailored cellular behaviors might help cells avoid environmental entrapment, which is relevant to cancer cell invasion, immune cell patrolling of peripheral tissues, and progenitor cell motility within a highly crowded cell mass of a developing embryo (33). The nuclear ruler mechanism defines an active function for the nucleus in cell migration, potentially explaining why enucleated cells show a poor motile capacity in dense collagen gels (34).…”
Section: Discussionmentioning
confidence: 99%
“…Relying on this ruler, cells can measure the degree of their environmental confinement and rapidly tailor specific behaviors to adapt to the confinement at time scales shorter than those associated with changes in gene expression. In the context of cell migration, such tailored cellular behaviors might help cells avoid environmental entrapment, which is relevant to cancer cell invasion, immune cell patrolling of peripheral tissues, and progenitor cell motility within a highly crowded cell mass of a developing embryo (33). The nuclear ruler mechanism defines an active function for the nucleus in cell migration, potentially explaining why enucleated cells show a poor motile capacity in dense collagen gels (34).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the better known mechanisms of mechanotransduction in adherent cells (which often involve Src), cells may use different mechanisms for sensing confinement 31 . This idea is supported by recent evidence that the INM unfolds and activates a cytosolic Phospholipase A2 (cPLA2)-dependent mechanotransduction pathway in confined cells, increasing actomyosin contractility 12,13 .…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, this phenotypic transition has been found to be promoted by cell confinement 7,8,10,11 . Although compressing the cell (i.e., confinement) may be sufficient to pressurize the cytoplasm, recent studies have suggested that cells adapt to confinement by upregulating actomyosin contractility 12,13 . Because of this dependence on confinement, rapid LBBM is likely to require the precise tuning of cell stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…She then discussed the effect of cortical tension on cell differentiation, showing that a decrease in tension correlates with, and is required for, the differentiation of embryonic stem cells via ERK signalling (De Belly et al, 2019). Verena Ruprecht (CRG Barcelona, Spain), building on her earlier study of a confinement-induced amoeboid mode of migration in embryonic zebrafish cells (Ruprecht et al, 2015), reported important advances on the identification of the signaling pathway that controls the switch between different modes of cell motility through nucleus deformation, calcium release and a mechanosensitive nuclear phospholipase (Venturini et al, 2019). Ulrich Schwarz (Heidelberg University, Germany) discussed an intriguing aspect of malaria infection, whereby Plasmodium falciparum orchestrates a "re-engineering" of the red blood cell cytoskeleton, making the cells switch from their canonical biconcave shape to a spherical one, and covering them in thousands of protrusions rich in parasite-generated adhesion molecules.…”
Section: Mechanics In Individual Cellsmentioning
confidence: 99%